Hubungan Antara Kemampuan Analisis Dan Kecemasan Siswa Menghadapi Tes Dengan Hasil Belajar Matematika SMP Di Jakarta - Kurnia Sari (Universitas Maritim AMNI Semarang, 2024)
This research aims to determine the relationship between students' problem analysis skills and students' anxiety about facing tests with mathematics learning outcomes in junior high school. This research was carried out on class VIII students at SMP Negeri 177 Jakarta. The model used in this research is descriptive correlational research to determine the relationship between problem analysis skills and students' anxiety in facing tests with mathematics learning outcomes. The method used is a survey method to obtain data directly from respondents with the independent variables being ability to analyze questions and students' anxiety facing tests and the dependent variable studied in the form of students' mathematics learning outcomes. The sampling technique used a cluster random sampling technique of 60 students from a previously determined affordable population. The data analysis technique uses multiple linear regression analysis. The multiple linear regression model obtained is = 32,1995 + 0,6490X1 - 0,1120X2. Test the hypothesis using the F-test and obtain Fcount = 12,622 while the Ftable value is 3,159, significance level a = 0,05. Based on the research results, it was found that there was a significant positive relationship between students' problem analysis skills and students' anxiety about facing tests together with mathematics learning outcomes. The partial correlation coefficient test obtained a calculated t-result of 4,633 with a t-table comparison of 1,672 between the ability to analyze questions and mathematics learning outcomes by assuming the test anxiety variable was constant, so it can be concluded that there is a significant positive relationship between students' ability to analyze questions and mathematics learning outcomes with assumes the variable of student anxiety facing a test is fixed. To find out whether there is a relationship between students' anxiety facing tests and their mathematics learning outcomes, by considering the variable of problem analysis ability to remain, the calculated t is -0,854 and the t-table is 1,672 so it can be concluded that there is no significant negative relationship between students' anxiety facing tests and their mathematics learning outcomes. Class VIII junior high school student at SMP N 177 Jakarta.